PENGARUH STOCK SPLIT TERHADAP ABNORMAL RETURN & LIKUIDITAS SAHAM BLUE CHIP - Pasaribu, Dedy Than (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Stock split is a corporate action intended to raise stock liquidity. When stock prices are high, the shares become inaccessible to all capital market investors. The impact of stock splits on abnormal returns and stock liquidity should be re-evaluated due to the discrepancies in prior studies. This research evaluates the influence of stock splits on liquidity and abnormal stock returns. This research utilized a sample of 27 blue-chip companies listed on the IDX that underwent stock splits from 2010 to 2022. Blue chip stocks are often the market leaders for each sector and subsector of stocks in the capital market. Variations in blue chip stocks can certainly have an impact on other common stocks in each sector and subsector. The Wilcoxon signed-rank test was used to assess differences. The study period spanned ten days, with five days before and five days after the stock split. This research discovered disparities in the abnormal returns and liquidity of the company shares that were part of blue-chip stocks before and after the stock split. This conclusion is based on the assumption that the abnormal returns and liquidity of stocks were consistent throughout the observation period (ceteris paribus).